Safety assessment of gemtuzumab ozogamicin: real-world adverse event analysis based on the FDA Adverse Event Reporting System - Liu, Xuexue; Wu, Fang; Li, Zhuoyan; Li, Chenxi; Li, Xinyu; Yuan, Yining; Sun, Xinyu; Du, Ying; Du, Xiao; Wang, Siliang; Xu, Peipei (Frontiers in Medicine, 2025)
ObjectiveTo mine adverse drug events (ADEs) following the use of gemtuzumab ozogamicin based on the FDA Adverse Event Reporting System (FAERS), and to provide references for the safety assessment of clinical drug use.MethodsWe obtained reports of adverse events with gemtuzumab ozogamicin as the main suspect from FAERS from within the first quarter of 2004 and the third quarter of 2024. The reporting odds ratio (ROR), comprehensive standard method (MHRA), Bayesian confidence propagation neural network (BCPNN) and multi-item gamma Poisson shrinker (MGPS) were applied to identify AE signals.ResultsA total of 2,065 patients were extracted. Screening for adverse drug events identified 238 positive signals. Among these, febrile neutropenia had the highest number of reports, while liver veno-occlusive disease (VOD) had the strongest signal intensity. Notably, our analysis revealed new high-risk signals, including cryptogenic organizing pneumonia (COP) and increased fibrin degradation products, which were not previously highlighted in FAERS analyses. These findings underscore the need for clinicians to closely monitor patients for these emerging risks, particularly in high-risk populations.ConclusionBy leveraging extensive real-world evidence from FAERS, we detected previously unidentified AEs linked to gemtuzumab ozogamicin via disproportionality analysis. Our results highlight the necessity for clinicians and pharmacists to prioritize the effective handling of this agent’s high-risk AEs, enhance its rational use in clinical settings, and safeguard patient pharmacotherapy. The identification of new signals, such as COP and increased fibrin degradation products, underscores the importance of continuous pharmacovigilance and the need to update clinical guidelines to reflect these emerging risks.